A Systematic Literature Review of Transnational Islamic Education Ideology and Islamic Educational Institutions - Adam Majid Bahrudin; Rahmad Hakim (Systematic Literature Review Journal, 2026)
This study seeks to analyze the ideas and practices of transnational Islamic educational ideologies and their impact on Islamic educational institutions across diverse local settings. Employing a Systematic Literature Review (SLR) method, the research systematically reviews a range of relevant scholarly sources, including peer-reviewed journal articles, dissertations, and research reports published between 2014 and 2024. The findings demonstrate that transnational movements such as Salafism, the Muslim Brotherhood, and Hizbut Tahrir significantly influence curriculum design, religious orientation, and the institutional culture of Islamic education. Nevertheless, this influence does not operate in a straightforward or uniform manner; instead, it is shaped through continuous negotiation with local contexts, particularly via state regulations, sociocultural conditions, and adaptive educational practices. The study highlights that local actors actively reinterpret and mediate transnational ideological frameworks to align them with national educational policies and community needs. Overall, this research offers comprehensive insights into the complex interactions between transnational Islamic ideologies and the ongoing transformation of contemporary Islamic education in different socio-political environments.